(untitled) (Filološke pripombe, 2019)
In this article, we present one proposed periodisation of the history of the Macedonian written language, starting from the earliest times up to the present time. The periodisation shows that the Macedonian written language has continuity in its development. That is why we can nominate this continuity of the development of the Macedonian written language as a Macedonian written tradition, which has shaped the contemporary standardisation of the Macedonian written language in 1903 as well as its final standardisation in 1945.